CURRENT THREATS TO CYBER SECURITY: STRATEGIES FOR PROTECTING PERSONAL DATA IN THE DIGITAL AGE - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The development of digital technology has brought convenience to various aspects of life, but on the other hand, it has also given rise to increasingly complex cyber security threats. Personal data is now a prime target for attacks because it has high economic value and can be exploited for illegal purposes. The latest threats include phishing, malware, ransomware, data leaks, attacks on Internet of Things devices, and digital manipulation using deepfake technology. The complexity of these threats not only harms individuals, but also impacts organisational security, social stability, and public trust in the digital ecosystem. Therefore, personal data protection strategies are crucial in facing the ever-evolving dynamics of cyber attacks. Effective strategies for protecting personal data include the use of two-factor authentication, data encryption, regular system updates, and the use of artificial intelligence for early threat detection. In addition, improving public digital literacy plays a central role in preventing social manipulation, while legal regulations such as the Personal Data Protection Act are an important foundation for upholding individual privacy rights. With a combination of technology, regulation, and digital awareness, personal data security can be strengthened so that the risk of cyber threats can be minimised. This study provides a comprehensive overview of current threats and offers adaptive mitigation strategies in the digital age.